Morphological caste differences in the neotropical swarm-founding polistinae wasps: Agelaia m. a. multipicta and a. p. pallipes (hymenoptera vespidae) - Noll, F. B.; Zucchi, R.; Simões, D. [UNESP] (Taylor & Francis, 1997)
Distinct size dimorphism was found between queens (inseminated egglayers) and workers (uninseminated non egg-layers) sampled from mature colonies of Agelaia pallipes and A. A. multipicta. In both species, among 22 measured body parts queens were larger than workers in 17 characters. The Mahalanobis' distance (D2) between castes was 122.74 in A. pallipes and 110.99 in A. A. multipicta, giving clear-cut evidence of caste separation, a conclusion which is strengthened by the absence of intermediate females. Comparisons with A. vicina and A. flavipennis demonstrated that morphological castes attributes are less developed in A. pallipes and A. A. multipicta. © 1997 Taylor & Francis Group, LLC.
Keywords: Agelaia multipicta; Agelaia pallipes; Caste differences; Multivariate analysis; Polistinae; Vespidae